Principles and practice of forensic psychiatry - Rosner, Richard; Scott, Charles; Taylor and Francis (Boca Raton, FL : CRC Press, an imprint of Taylor and Francis, 2017)
The third edition of this award-winning textbook has been revised and thoroughly updated. Building on the success of the previous editions, it continues to address the history and practice of forensic psychiatry, legal regulation of the practice of psychiatry, forensic evaluation and treatment, psychiatry in relation to civil law, criminal law and family law, as well as correctional forensic psychiatry. New chapters address changes in the assessment and treatment of aggression and violence as well as psychological and neuroimaging assessments.
Includes bibliographical references and index.
Also available in print format.
Keywords: Forensic psychiatry -- United States; Forensic Psychiatry; Gerichtliche Psychiatrie; Electronic books